Production of monoclonal antibodies to Naegleria fowleri, agent of primary amebic meningoencephalitis. - Visvesvara, G S (1987)
Monoclonal antibodies (MAbs) to Naegleria fowleri, the etiologic agent of primary amebic meningoencephalitis (PAM), have been produced and used as probes to identify N. fowleri amebae in brain sections of patients who died of that disease. These MAbs were characterized for their specificity by the indirect immunofluorescence assay (IIF), dot immunobinding assay (DIBA), and enzyme-linked immunotransfer blot technique (EITB). The MAbs reacted intensely with all strains of N. fowleri tested originating from different geographic areas in the IIF and DIBA tests, but showed no reactivity with four other species of Naegleria, N. gruberi, N. jadini, N. lovaniensis, and N. australiensis, or a strain of Acanthamoeba castellanii. In the EITB assay the MAbs reacted with the antigens of N. fowleri and produced intensely staining bands at the 160-, 104-, 93-, and 66-kilodalton (kDa) regions and several minor bands at the 30- and 50-kDa regions. The MAbs also reacted with the antigens of N. lovaniensis and produced a darkly staining band at 160 kDa and a diffusely staining band at 116 kDa, indicating that these antigens were shared by the two species. The MAbs, however, showed no reactivity with N. jadini and N. gruberi in the EITB assay.